Performance Evaluation of Hybrid Fiber-Reinforced Inorganic Mortar for Textile-Reinforced Mortar Applications - Manisha Shewale; P. Murthi; R. Siva Chidambaram; R. Gobinath (Advances in Civil Engineering)
The need to improve existing structures has led to extensive research on strengthening techniques. Textile-reinforced mortar (TRM) systems, which involve the integration of high-strength fibers with inorganic matrix, have emerged as a highly promising and viable alternative. The objective of this research is to investigate the mechanical characteristics of inorganic mortar by examining different compositions involving sand, fibers, and cementitious materials. Various combinations were tested to evaluate their compressive strength, split tensile strength, and flexural strength. The findings indicated that a composite mixture (sample 12) comprising microsilica, silica sand, and optimized fibers demonstrated enhanced strength in all three assessments. Research highlights the significance of accurate mixing, additional components, and appropriate fibers to achieve intended performance of the mortar. The compatibility of the mortar is checked with substrate surface and textile sheet. Mortar is evaluated for splitting bond strength, slant shear test, direct pull-off bond strength, and pull-out strength. These results provide information about the strength and bonding characteristics of the mortar in different test scenarios. Values indicate how well the mortar performs with the substrate surface and the textile sheet under various types of stresses and loading conditions.